Efficacy and Safety of Locally Injected Tranexamic Acid in Hip Fracture Patients: A Retrospective Review. Issue 3 (March 2022) - Witmer, Daniel; Solomito, Matthew J.; Kumar, Mandeep; Shearier, Emily; Davis, Stephen
Abstract : Objective: To determine whether locally injected tranexamic acid (TXA) used in the surgical treatment of fragility hip fractures can lower transfusion rates without increasing the risk of complications. Design: Retrospective comparative cohort. Setting: Tertiary referral orthopaedic specialty hospital, Level I trauma center. Patients/Participants: A total of 490 patients (252 patients received TXA) 50 years of age and older who underwent surgery for a low-energy fragility fracture of the proximal femur between March 2018 and February 2020 were included in this study. Intervention: Use of locally injected TXA at the time of wound closure. Main Outcome: The main outcomes of this study were the number of patients requiring postoperative blood transfusions, incidences of venous thromboembolism, and surgical site infections. Results: A statistically significant difference was noted in the frequency of transfusion between patients who received TXA compared with those who did not receive TXA (33% vs. 43%, respectively) ( P = 0.034). There were no significant differences in venous thromboembolism incidence (0.4% vs. 0.8% TXA vs. No TXA) ( P = 0.526) or infections (0.4% vs. 0.4% TXA vs. No TXA) ( P = 0.965). Regression analysis indicated that the use of TXA reduced the need for postoperative blood transfusion by 31% (odds ratio: 0.688, 95% CI: 0.477–0.993, P = 0.045). Conclusion: Locally injected TXA significantly reduced the need for postoperative transfusion in the surgical treatment of fragility hip fractures. In addition, there was no increased risk of complications in those receiving TXA versus those who did not. Locally injected TXA seems to be both a safe and effective way to reduce postoperative blood transfusions in patients with fragility hip fractures. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.